1999
DOI: 10.1083/jcb.144.4.617
|View full text |Cite
|
Sign up to set email alerts
|

Processing of Endogenous Pre-mRNAs in Association with SC-35 Domains Is Gene Specific

Abstract: Analysis of six endogenous pre-mRNAs demonstrates that localization at the periphery or within splicing factor-rich (SC-35) domains is not restricted to a few unusually abundant pre-mRNAs, but is apparently a more common paradigm of many protein-coding genes. Different genes are preferentially transcribed and their RNAs processed in different compartments relative to SC-35 domains. These differences do not simply correlate with the complexity, nuclear abundance, or position within overall nuclear space. The di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
188
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(213 citation statements)
references
References 49 publications
25
188
0
Order By: Relevance
“…The approach that we have employed uses natural cellular mechanisms to introduce nucleotide analogs into intact cells+ We show that FuGene-6, in addition to functioning as a transfectant for plasmids, efficiently and rapidly mediates the uptake of the halogenated base analog BrUTP into cultured cells+ Although other lipid transfection reagents have been successfully used as vectors for the uptake and incorporation of BrUTP into growing cells (Haukenes et al+, 1997;Kanestrom et al+, 1998), we demonstrate that lipofection with BrUTP can be a useful tool for studying transport of newly labeled rRNAs in intact cells either within the nucleus or from the nucleus to the cytoplasm+ In summary, this nondestructive method presents several decisive advantages which permits (1) the complementary ultrastructural and optical investigations of the sites in which rRNA elongation and processing take place by using the same labeling conditions; (2) a more resolved ultrastructural identification of the nucleolar components containing the BrUTP-labeled RNAs, compared to previous autoradiographic studies (Fakan, 1978; (3) the detailed analysis of the volumic organization of the nucleolar components containing the BrUTP-labeled RNAs and of their modification along time by using confocal microscopy, three-dimensional reconstruction, and visualiza- Our ultrastructural data demonstrate that ribosome biogenesis starts in the FC and in the inner part of the DFC, then migrates rapidly in the outer part of the DFC and in the GC+ The three-dimensional reconstruction and visualization, by giving a global view, clearly indicate that the transport of rRNAs within the nucleolus occurs neither randomly nor along tracks as for some mRNA (Lawrence et al+, 1989;Smith et al+, 1999)+ On the contrary, we demonstrate that transport of rRNA follows a volumic, well-defined pathway from the inner part of the nucleolus toward its periphery+ This migration can be summarized by four typical labeling patterns, which could correspond to four main functional domains+…”
Section: The Approach For Identifying Both Transcription and Processimentioning
confidence: 89%
“…The approach that we have employed uses natural cellular mechanisms to introduce nucleotide analogs into intact cells+ We show that FuGene-6, in addition to functioning as a transfectant for plasmids, efficiently and rapidly mediates the uptake of the halogenated base analog BrUTP into cultured cells+ Although other lipid transfection reagents have been successfully used as vectors for the uptake and incorporation of BrUTP into growing cells (Haukenes et al+, 1997;Kanestrom et al+, 1998), we demonstrate that lipofection with BrUTP can be a useful tool for studying transport of newly labeled rRNAs in intact cells either within the nucleus or from the nucleus to the cytoplasm+ In summary, this nondestructive method presents several decisive advantages which permits (1) the complementary ultrastructural and optical investigations of the sites in which rRNA elongation and processing take place by using the same labeling conditions; (2) a more resolved ultrastructural identification of the nucleolar components containing the BrUTP-labeled RNAs, compared to previous autoradiographic studies (Fakan, 1978; (3) the detailed analysis of the volumic organization of the nucleolar components containing the BrUTP-labeled RNAs and of their modification along time by using confocal microscopy, three-dimensional reconstruction, and visualiza- Our ultrastructural data demonstrate that ribosome biogenesis starts in the FC and in the inner part of the DFC, then migrates rapidly in the outer part of the DFC and in the GC+ The three-dimensional reconstruction and visualization, by giving a global view, clearly indicate that the transport of rRNAs within the nucleolus occurs neither randomly nor along tracks as for some mRNA (Lawrence et al+, 1989;Smith et al+, 1999)+ On the contrary, we demonstrate that transport of rRNA follows a volumic, well-defined pathway from the inner part of the nucleolus toward its periphery+ This migration can be summarized by four typical labeling patterns, which could correspond to four main functional domains+…”
Section: The Approach For Identifying Both Transcription and Processimentioning
confidence: 89%
“…The components of higher order nuclear architecture, including nuclear pores [22], the nuclear matrix, and subnuclear domains, contribute to the subnuclear distribution and activities of genes and regulatory factors [21,23]. Compartmentalization of regulatory complexes is illustrated by focal organization of PML bodies [24], Runx bodies [25,26], the nucleolus [27], and chromosomes [28], as well as by the punctate intranuclear distribution of sites for replication [29], DNA repair [30], transcription [31], and the processing of gene transcripts [32][33][34]. There is emerging recognition that nuclear structure and function are casually related.…”
Section: Vitamin D-mediated Gene Expression Within the Three Dimensiomentioning
confidence: 99%
“…On the other hand, it has been shown that nascent mRNA transcripts and transcription sites are closely associated with speckles, that transcription occurs at the surface of speckles (Clemson and Lawrence, 1996), and that microinjected pre-mRNAs have high affinity to speckles (Wang et al, 1991). It has thus been proposed that speckles can act coordinately in transcription and splicing and that pre-mRNA splicing can take place both at the periphery and inside speckles (Smith et al, 1999;Wei et al, 1999). A model combining both views suggests that splicing factors are recruited to transcription sites, whereas certain mRNAs are released from such sites and associate with splicing factor reservoirs (Melcak et al, 2000).…”
mentioning
confidence: 99%